The Role of Artificial Intelligence in Pharmaceutical Sales and Marketing: A Recent Study - Bayoun, Dana (Global journal of Business and Integral Security, 2026)
The term artificial intelligence (AI) refers to the way professionals recently perceive a computer-controlled robot, whether an intelligent machine, or software. Matching healthcare professionals and placing them on the appropriate channel at the appropriate moment will be the main goals of the sales and marketing teams. AI will help marketing teams with full analysis from brand diagnostics, brand history analysis, and future brand planning and strategy. Furthermore, AI could give sales teams a competitive edge and enhance sales results by assisting them with guided sales, pre-call planning, e-detailing, and Customer Relationship Management (CRM). This will help Pharma businesses produce better results using less time and resources. Additionally, it can be helpful for patients to follow their treatment plans and adherence. The aim and purpose of this paper is to seek new ways using AI to boost sales and marketing efforts in the pharmaceutical market which can help new entrepreneurs and better strategic approach and implementation.